Cross-cutting Issues in the Practice of Pediatricians and Infectionists - A. A. Cheburkin; L. N. Mazankova; A. P. Prodeus (LLC "Diagnostics and Vaccines", 2016)
18-19 May 2016 in Moscow hosted the annual IX Sientific-practical conference «Infectious Aspects of Somatic Diseases in Children».